Bone Cement and Pedicle Screw for the Treatment of Spinal Tumors with Spinal Cord Compression and Posterior Wall Defects. Issue 8 (6th July 2022) - Shao, Xiaofeng; Wu, Jian; Zhou, Zhangzhe; Lv, Nanning; Chen, Kangwu; He, Shuangjun; Sun, Zhiyong; Qian, Zhonglai
Abstract : Objective: To compare the safety and efficacy of posterior internal fixation with open vertebroplasty (VP) and posterior internal fixation with open kyphoplasty (KP) in the treatment of metastatic epidural spinal cord compression (MESCC) with posterior wall destruction. Methods: This retrospective study, conducted between January 2016 and May 2019, equally divided 60 patients with MESCC and posterior wall destruction into two groups based on the surgical method: open vertebroplasty with pedicle screw fixation (VP group) and open kyphoplasty with pedicle screw fixation (KP group). Visual analogue scale (VAS), SF‐36 scores, middle vertebral height (MVH), and posterior vertebral height (PVH) were evaluated for the two groups preoperatively, postoperatively, and 1 year after surgery. Spinal Instability Neoplastic Score, Frankel grades and complications were recorded and evaluated. Results: Five patients were excluded from the analysis, and our study cohort consisted of 55 adult patients who met the inclusion criteria. The VAS and SF‐36 scores of these two groups of patients significantly improved, when compared with those before the surgery ( P < 0.05). There were significant differences in total cost (8835 ± 1468 vs 9540 ± 053 USD) and cement volume (4.51 ± 0.96 ml vs 6.35 ± 1.09 ml) between two groups ( P < 0.05). The MVH and PVH of these two groups of patients significantly improved, when compared with those before the surgery ( P < 0.05). The MVH was significantly larger in the KP group than in the VP group postoperatively (20.15 ± 4.86 vs 17.70 ± 3.78, P < 0.05) and at the final follow‐up (20.42 ± 5.59 vs 17.28 ± 3.23, P < 0.05). However, the PVH of the two groups did not significantly differ at the two postoperative follow‐ups ( P > 0.05). No significant differences were found in surgery time, time from surgery to discharge, blood loss and complications between both groups postoperatively ( P > 0.05). Conclusion: In the short term, both approaches are effective and safe in patients with MESCC and posterior wall destruction. The posterior internal fixation with open VP may be a good choice of surgical method in patients with MESCC and posterior wall defects. Abstract : (A) The tumor tissue involved the posterior wall and invade the vertebral canal to compress the spinal cord. (B) The pedicle screws were placed at the levels above and below the targeted vertebra. The vertebroplasty was then performed through a transpedicular approach. (C) The sextant rods were placed and nut was locked.